Geoffrey of Monmouth and the Translation of Female Kingship - Tolhurst, F. author. aut Link
X, 347 p.
Keywords: Geoffrey of Monmouth and the Translation of Female Kingship provides the first feminist analysis of the part of The History of the Kings of Britain that most readers overlook: the reigns before and after Arthur's.